Effect of ascorbate and hydrogen peroxide on hormone and metabolite levels during post-germination growth in wheat - Asghar, Muhammad Ahsan; Kulman, Kitti; Szalai, Gabriella; Gondor, Orsolya Kinga; Mednyánszky, Zsuzsa; Simon-Sarkadi, Livia; Gaudinova, Alena; Dobrev, Petre I; Vanková, Radomíra; Kocsy, Gábor (Physiologia plantarum, 2023)
The modulation of hormone and metabolite levels by ascorbate (ASA) and hydrogen peroxide (H2 O2 ) was compared during post-germination growth in shoots of wheat. Treatment with ASA resulted in a greater reduction of growth than the addition of H2 O2 . ASA also had a larger effect on the redox state of the shoot tissues as shown by the higher ASA and glutathione (GSH) levels, lower glutathione disulfide (GSSG) content and GSSG/GSH ratio compared to the H2 O2 treatment. Apart from common responses (i.e., increase of cis-zeatin and its O-glucosides), the contents of several compounds related to cytokinin (CK) and abscisic acid (ABA) metabolism were greater after ASA application. These differences in the redox state and hormone metabolism following the two treatments may be responsible for their distinct influence on various metabolic pathways. Namely, the glycolysis and citrate cycle were inhibited by ASA and they were not affected by H2 O2 , while the amino acid metabolism was induced by ASA and repressed by H2 O2 based on the changes in the level of the related carbohydrates, organic and amino acids. The first two pathways produce reducing power, while the last one needs it; therefore ASA, as a reductant may suppress and induce them, respectively. H2 O2 as an oxidant had different effect, namely it did not alter glycolysis and citrate cycle, and inhibited the formation of amino acids.
Keywords: Ascorbic Acid; aminokyseliny; glutathion; Amino Acids; hormony; Triticum; kyselina askorbová; Germination; pšenice; Hydrogen Peroxide; klíčení; peroxid vodíku; glutathiondisulfid; Glutathione Disulfide; Hormones; Glutathione